Learning Leadership from Batik Cloth: A Symbolic Study of the Semén Rama Motif - Veronika Agustini Srimulyani; Yustinus Budi Hermanto (International Journal Of Community Service, 2025)
Batik is not just a cloth with beautiful motifs, because behind the elegance of the motifs or patterns, there are philosophical meanings that reflect the cultural values, history, and identity of the Indonesian nation. Common motifs used in classical batik such as the Semén Rama motif, which is associated with the Javanese palaces, especially Yogyakarta and Surakarta, are not only aesthetically appealing, but also symbolize various aspects of Javanese philosophy, social order, spirituality, leadership, wisdom, purity, and noble character as important elements in the development of human personality. The Javanese leadership ethos studied from the Semén Rama motif is Astha Brata, which contains eight elements of the universe), namely: earth/soil, sun, fire, ocean/sea, sky, wind, moon, and stars (cosmocentric) or 8 (eight) characters and actions or eight (8) gods, namely: Endra, Surya, Bayu, Kuwera, Baruna, Yama, Chandra, and Brahma, are universal and up to date, as a reflection of noble values that are always in the midst of human life. Leaders can reflect on the eight elements of nature so that their leadership practices can run well and be successful in accordance with the development of the path and in line with the contents of the universe which have been systematically arranged by Almighty God.